Privacy-Preserving Patient Tracking for Phase 1 Clinical Trials - Farah, Hanna Ibrahim (Université d'Ottawa / University of Ottawa, 2015)
Electronic data has become the standard method of storing information in our modern age. Evolving from paper-based data to electronic data creates opportunities to share information between organizations in record speeds, especially when handling large data sets. However, sharing sensitive information creates requirements for electronic data exchange: privacy requires that the original data will not be revealed to unauthorized parties. In the healthcare sector in particular, there are two important use cases that require exchanging information in a privacy-preserving way. 1. Contract research organizations (CROs) need to verify the eligibility of a participant in a phase 1 clinical trial. One criterion is checking that an individual is not concurrently enrolled in a trial at another CRO. However, privacy laws and the maintenance of a private list of participants for competitive purposes prevent CROs from checking against that criterion. 2. A patient’s medical record is usually distributed amongst several healthcare organizations. To improve healthcare services, it is important to have a patient’s complete medical history: either to help diagnose an illness or to gather statistics for better disease control. However, patient medical files need to be confidential. Two healthcare organizations cannot link their large patient databases by disclosing identity revealing details (e.g., names or health card numbers). This thesis presents the development and evaluation of protocols capable of querying and linking datasets in a privacy-preserving manner: TRACK for checking concurrent enrolment in phase 1 clinical trials, and SHARE for linking two large datasets in terms of millions of (patient medical) records. These protocols are better than existing approaches in terms of the privacy protection level they offer (e.g., against dictionary and frequency attacks), of the reliance on trusted third parties, and of performance when performing blocking. These protocols were extensively validated in simulated scenarios similar to their real-world counterparts. The thesis presents novel identity representation schemes that offer strong privacy measures while being efficient for very large databases. These schemes may be used by other researchers to represent identity in different use cases. CROs may implement the protocols (and especially TRACK) in systems to check if an individual exists in another CRO’s dataset without revealing the identity of that individual. Two healthcare organizations may use a system based on this research (and especially the SHARE protocol) to discover their common patients while protecting the identities of the other patients.
Keywords: Privacy; Private record linkage; Clinical trials; Secure multi-party computation; Private blocking; Identity